ADVOCACY IMPLEMENTATION, COMMUNICATION, SOCIAL MOBILIZATION IN THE HEALTH DEVELOPMENT PROGRAM. [A THEORETICAL REVIEW] - Muh. Zainal S. (Universitas Muhammadiyah Jakarta, 2019)
Health problems become responsibility of all elements of society, not only government. Support and involvement from all stakeholders are crtitical to overcome many of health problems in the context of development and social change. This article aims to produce descriptive theoretical advocacy, communication, social mobilization and research findings that are relevant to Advocacy, Communication and Social Mobilization (AKMS). This study used a literature study approach (desk study) by collecting documents and literature relevant to the topic of the article. Based on literature studies, it can be concluded that advocacy, communication and social mobilization activities are interrelated. Advocacy is an approach to securing economic resource needs and policy changes, by influencing stakeholders, the private sector, community elements, including the media. Meanwhile, communication seeks to increase awareness, influence social norms, create changes in the behavior of individuals or a community through communication channels both interpersonal (counseling), mass media and the internet including social media. Furthermore, social mobilization is concerned with efforts to gather social support to change norms, improve services, expand community support and solve social problems. Keywords: Advocacy, Communication, Social Mobilization